Epidermolysis Bullosa Simplex – Dowling-Meara Type: A Case Report in a 10-year-old Boy - Linza P. Zachariah; Betsy Ambooken; Raghavendra Rao; Neelakandhan Asokan (Indian Journal of Paediatric Dermatology, 2024)
Epidermolysis bullosa simplex – Dowling-Meara type (EBS-DM) is characterized by the presence of bullae and vesicles with arcuate borders in a herpetiform manner at the trauma-prone areas of the body since birth. Here we report the clinical course of EBS-DM in a 10-year-old boy. We confirmed the diagnosis by antigen mapping which showed clumping of keratin 14 with decreased staining in few areas.